Crocetin imparts antiproliferative activity via inhibiting STAT3 signaling in hepatocellular carcinoma. Issue 11 (23rd September 2021) - Mohan, Chakrabhavi Dhananjaya; Kim, Chulwon; Siveen, Kodappully Sivaraman; Manu, Kanjoormana Aryan; Rangappa, Shobith; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Rangappa, Kanchugarakoppal S.; Kumar, Alan Prem; Ahn, Kwang Seok
Abstract: STAT3 is a key oncogenic transcription factor, often overactivated in several human cancers including hepatocellular carcinoma (HCC). STAT3 modulates the expression of genes that are connected with cell proliferation, antiapoptosis, metastasis, angiogenesis, and immune evasion in tumor cells. In this study, we investigated the effect of crocetin on the growth of HCC cells and dissected its underlying molecular mechanism in imparting a cytotoxic effect. Crocetin suppressed proliferation, promoted apoptosis, and counteracted the invasive capacity of HCC cells. Besides, crocetin downregulated the constitutive/inducible STAT3 activation (STAT3 Y705 ), nuclear accumulation of STAT3 along with suppression of its DNA binding activity in HCC cells with no effect on STAT5 activation. Crocetin suppressed the activity of upstream kinases such as Src, JAK1, and JAK2. Sodium pervanadate treatment terminated the crocetin‐propelled STAT3 inhibition suggesting the involvement of tyrosine phosphatases. Crocetin increased the expression of SHP‐1 and siRNA‐mediated SHP‐1 silencing resulted in the negation of crocetin‐driven STAT3 inhibition. Further investigation revealed that crocetin treatment inhibited the expression of STAT3 regulated genes (Bcl‐2, Bcl‐xL, cyclin D1, survivin, VEGF, COX‐2, and MMP‐9). Taken together, this report presents crocetin as a novel abrogator of the STAT3 pathway in HCC cell lines.